2020
DOI: 10.1016/j.redox.2020.101627
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nrf2/Keap1 signalling in human skeletal muscle during exercise to exhaustion in normoxia, severe acute hypoxia and post-exercise ischaemia: Influence of metabolite accumulation and oxygenation

Abstract: The Nrf2 transcription factor is induced by reactive oxygen and nitrogen species and is necessary for the adaptive response to exercise in mice. It remains unknown whether Nrf2 signalling is activated by exercise in human skeletal muscle. Here we show that Nrf2 signalling is activated by exercise to exhaustion with similar responses in normoxia (P I O 2 : 143 mmHg) and severe acute hypoxia (P I O 2 : 73 mmHg). CaMKII an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 85 publications
1
34
0
Order By: Relevance
“…The ratio of Nrf2-ARE binding to Keap1 content also illustrates the relationship between Keap1 protein and Nrf2-ARE binding. A recently published paper reported significant decreases in Keap1 content after acute exhaustive exercise in human skeletal muscle and concomitant increases in Nrf2 [17], our data here are in agreement with these results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The ratio of Nrf2-ARE binding to Keap1 content also illustrates the relationship between Keap1 protein and Nrf2-ARE binding. A recently published paper reported significant decreases in Keap1 content after acute exhaustive exercise in human skeletal muscle and concomitant increases in Nrf2 [17], our data here are in agreement with these results.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on Nrf2 signaling responses to exercise have used whole animal treadmill exercise, measuring Nrf2 in several different tissues [2,15,16,[31][32][33][34][35][36][37], or whole-body exercise in humans [1,17,24,25,[38][39][40]. We have recently shown that basal levels of Nrf2 affect its inducibility to an acute exercise bout in humans [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the transcription factor NF-E2 p45-related factor 2 (Nrf2) and the E3 ligase adaptor Kelch-like ECH-associated protein 1 (KEAP1), which is the primary negative regulator of Nrf2, are both critical players in redox homeostasis, the antioxidative response, and mitochondrial biogenesis. It was recently shown that acute exercise increases the total Nrf2 protein content within minutes after an exercise bout (Gallego-Selles et al, 2020), but less is known regarding the chronic response to training.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 CaMKII regulates the expression of the transcription factor coactivator peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), which is a critical regulator of mitochondrial biogenesis. 4 Besides this, CaMKII has been implicated in the regulation of the transcription factor nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), 5,6 which is stimulated by high-intensity exercise 7 and muscle metabolism. [8][9][10] Nevertheless, previous evidence on the role of CaMKII in the regulation of muscle phenotype comes from extreme experimental models and information using physiological models in humans is lacking.…”
Section: Introductionmentioning
confidence: 99%